(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
As the chip area is reducing every day the usual transistor model CMOS method suffers with heavy problems because of channel properties such as very low lean gate oxides, increased channel effects, induced drain leakage currents and high power consumption at nano tech standards. Quantum-Dot-Cellular-Automata (QCA) is an advanced technology implemented at quantum levels, it gives an entirely special implementation proposal to develop every integrated circuit based applications utilizing four quantum holes combined in forbidden shell to successfully progress and transmit data at nano tech standards as an opponent of conventional CMOS methodology. In this article, various sequential circuits are designed such as D-FLIP FLOP (FF), T-FF, SR-FF, JK-FF, Shift registers and universal counters. The implementation and simulation results developed using Xilinx ISE simulation tool and results shows that the proposed designs provides the enhanced results compared to the conventional approaches.